2011
DOI: 10.1097/pgp.0b013e31821f4b85
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis and Ovarian Cancer

Abstract: Summary Endometriosis is a chronic disease that affects millions of reproductive-age women. Despite the destructive and invasive nature of endometrioses, most cases are perpetually benign or eventually regress; however, atypical endometriosis is a precursor lesion and can lead to certain types of ovarian cancer. Endometriosis induced inflammation and auto- and paracrine production of sex steroid hormones contribute to ovarian tumorigenesis. These changes provide microenvironment necessary to accumulate enough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
105
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(111 citation statements)
references
References 109 publications
3
105
0
3
Order By: Relevance
“…This association has later been reported in several studies [3,4,5,6,7], particularly for endometriosis with ovarian endometrioid and clear cells carcinomas, suggesting that concurrent endometriosis is generally associated with a better prognosis for these specific subtypes of EOC [8,9,10]. Moreover, atypical endometriosis has been described as a precursor lesion that can lead to certain types of ovarian cancer [11,12,13,14,15]. Other authors have also suggested a hormonal dependence or a relationship with other hormone-dependent pathologies in this type of association [16,17].…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…This association has later been reported in several studies [3,4,5,6,7], particularly for endometriosis with ovarian endometrioid and clear cells carcinomas, suggesting that concurrent endometriosis is generally associated with a better prognosis for these specific subtypes of EOC [8,9,10]. Moreover, atypical endometriosis has been described as a precursor lesion that can lead to certain types of ovarian cancer [11,12,13,14,15]. Other authors have also suggested a hormonal dependence or a relationship with other hormone-dependent pathologies in this type of association [16,17].…”
Section: Introductionmentioning
confidence: 90%
“…On the other hand, atypical endometriosis is considered to be precancerous and strongly associated with endometriosis-associated ovarian cancer [15], although recognition of this form of endometriosis as a diagnostic criterion for pathological and clinical management remains controversial. Czernobilsky and Morris [11] first described atypical endometriosis, and Thomas and Campbell [19] further classified it based on the features that were identified in histological examinations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations